Рабыня страсти: роман / Бертрис Смолл; [пер. с англ. А. Медниковой] - Смолл Бертрис (Шарм, 2002)
Экземпляры: ф.22 (2002) / Инвентарный номер: 43738 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: С 51 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44